Penguasaan Konsep Kursus Operating System (DFC2063) dalam Kalangan Pelajar Politeknik Sultan Mizan Zainal Abidin - Efeza Che Apandey; Shaifatul’ Ain Mohamad (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2018)
This action study was conducted to address the underlying causes of underperforming the operating system concept for the Operating System (DFC 2063) course. The respondents involved were 30 students of the 1st semester of Digital Technology Diploma Program, Department of Information and Communication Technology, Polytechnic of Sultan Mizan Zainal Abidin. The purpose of this study is to identify the basic knowledge of the students to understand the concept of operating system, the source of the students' weakness in the concept of operating system, the mastery of the students in the concept of operating system and the interest of students in the concept of operating system. The research method used is quantitative and qualitative study method. The data collection was done through questionnaire and interview session. The results of this study showed that 70% of respondents did not have basic knowledge about the operating system. This finding is further supported by 73% of respondents acknowledging the impersonation of lecturers. Implementation of the action is carried out within a month by holding focused exercises using past exam questions and emphasizing on topics that are deemed difficult to master by students. Lecturers also show compilation of related P & P videos to enhance student understanding and diversify teaching techniques in the classroom. The result is that there is a 40% increase in students who get grade A and no students are getting grade D. In conclusion, the implementation of the action has a positive impact and can be suggested for the next level.